If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3y = 2x + 1 Reorder the terms: 9x + -3y = 1 + 2x Solving 9x + -3y = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9x + -2x + -3y = 1 + 2x + -2x Combine like terms: 9x + -2x = 7x 7x + -3y = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 7x + -3y = 1 + 0 7x + -3y = 1 Add '3y' to each side of the equation. 7x + -3y + 3y = 1 + 3y Combine like terms: -3y + 3y = 0 7x + 0 = 1 + 3y 7x = 1 + 3y Divide each side by '7'. x = 0.1428571429 + 0.4285714286y Simplifying x = 0.1428571429 + 0.4285714286y
| 4x-9=-3 | | 5x+8=5x-3 | | 4a-16= | | -2(x+2)=-16 | | 3x+3=7x-5 | | 4a-16=21a | | x/9=-11 | | 3[9-(-7x-6)]=168x+171 | | 3x+15=x+5 | | 55-x=63 | | -3(x-1)=2(x-11) | | 17m-4=8m+8+m | | 6+8b=78 | | 7-6x=12-2x | | (7x+8)(2x-11)=0 | | 3x+3x-5=25 | | 2x+20=5x-10 | | 5[4(3x-2)+9x]-7(x+5)=170 | | 5x+8-7(x+1)=7x+8 | | (x+3)=18 | | 9r^3=36r | | 3x-11+2x-2=9x+27 | | 9x+27+2x-2=3x-11 | | 2-(3x-23)=5(x-2) | | 2x-2=9x+27 | | 2(-5)12/3= | | 12x+16=9x+27 | | 12-(-5)= | | 12x+16=2x-2 | | U=LWH | | 19=4X+5-2X | | 3x-11=2x-2 |